21-Gene assay as predictor of chemotherapy benefit in HER2-negative breast cancer. (December 2018) - Geyer, Charles; Tang, Gong; Mamounas, Eleftherios; Rastogi, Priya; Paik, Soonmyung; Shak, Steven; Baehner, Frederick; Crager, Michael; Wickerham, D.; Costantino, Joseph; Wolmark, Norman
Abstract The NSABP B-20 prospective-retrospective study of the 21-gene Oncotype DX Breast Cancer Recurrence Score® test predicted benefit from addition of chemotherapy to tamoxifen in node-negative, estrogen-receptor positive breast cancer when recurrence score (RS) was ≥31. HER2 is a component of the RS algorithm with a positive coefficient and contributes to higher RS values. Accrual to B-20 occurred prior to routine testing for HER2, so questions have arisen regarding assay performance if HER2-positive patients were identified and excluded. We report an exploratory reanalysis of the B-20, 21-gene study following exclusion of such patients. Patients were considered HER2 positive if quantitative RT-PCR for HER2 was ≥11.5 units, and excluded from re-analyses performed using the original cutoffs: <18, 18–30, ≥31, and the TAILORx cutoffs: <11, 11–25, >25. The endpoint remained distant recurrence-free interval (DRFI) as in the original study. Distribution was estimated via the Kaplan–Meier method and compared via log-rank test. Multivariate Cox proportional hazards models estimated chemotherapy benefit in each group. In the RS < 18 and 18–30 groups, 1.7 and 6.7% were HER2 positive. In the RS ≥ 31 group, 41% were HER2 positive. Exclusion resulted in fewer events, with loss of significance for benefit from chemotherapy in the overall HER2-negative cohort (log-rankP = 0.06), but substantial benefit from chemotherapy remained in the RS ≥ 31 cohort (HR = 0.18; 95% CI: 0.07–0.47) and the RS > 25 cohort (HR = 0.28; 95% CI: 0.12–0.64). No benefit from chemotherapy was evident in the other RS groups. Following exclusion of HER2-positive patients based on RT-PCR expression, substantial benefit of chemotherapy remained for RS ≥ 31 as originally employed, and with RS > 25 employed in TAILORx. Genetics: multigene panel predicts chemo benefit regardless of HER2 status A commonly used genetic test helps to predict whether patients with estrogen-receptor positive, node-negative breast cancer stand to gain from chemotherapy. Charles Geyer from NRG Oncology/NSABP and Virginia Commonwealth University and colleagues reanalyzed data from a decades-old study that helped establish a 21-gene panel as a tool for determining whether to add chemotherapy to endocrine therapy for women with estrogen-receptor positive, node-negative breast cancer. The researchers excluded patients with HER2-positive disease becauseHER2 gene expression is part of the diagnostic test and questions have persisted regarding the performance of the assay, if HER2-positive patients were excluded. This new analysis demonstrated that although chemotherapy did not extend disease-free survival overall among the cohort of patients with HER2-negative disease, it still proved beneficial for those with high recurrence scores on the genetic test. The findings thus validate the clinical utility of the test for patients with estrogen-receptor positive, HER2-negative, node negative breast cancers.